Antithrombotic Management during Percutaneous Mitral Valve Repair with the Mitraclip System in a Patient with Heparin-Induced Thrombocytopenia - Saia, Francesco; Biagini, Elena; Berardini, Alessandra; Chiarabelli, Matteo; Bertolino, Emanuela; Compagnone, Miriam; Rapezzi, Claudio (TH Open, 2018)
Interventional cardiology procedures require full anticoagulation to prevent thrombus formation on catheters and devices with potential development of embolic complications. Bivalirudin, a short half-life direct thrombin inhibitor, has been largely used during percutaneous coronary interventions and represents the preferred alternative to heparin in patients with heparin-induced thrombocytopenia (HIT). However, few data are available about intraprocedural use of bivalirudin during transcatheter structural heart disease interventions. Activated clotting time (ACT) monitoring during bivalirudin infusion presents some limitations and it is not mandatory. We report a case of bivalirudin use in a patient with type-2 HIT during percutaneous mitral valve repair with the Mitraclip system (Abbott, Abbott Park, Illinois, United States). Despite use of standard bivalirudin dose (0.75 mg/kg bolus and 1.4 mg/kg/min infusion—reduced infusion rate was motivated by a glomerular filtration rate of 37 mL/min), the patient developed a large thrombus on the second clip during its orientation toward the mitral orifice. ACT was measured at that time and was suboptimal (240 seconds). The case was successfully managed with clip and thrombus retrieval, adjunctive 0.3 mg/kg bivalirudin bolus and increased infusion rate, and clip repositioning with ACT monitoring. This report makes the case for mandatory ACT checking and drug titration during high-risk catheter–based structural heart disease interventions, even when thromboprophylaxis is performed with bivalirudin. Additional coagulation tests may be useful to monitor bivalirudin response in similar cases.
Keywords: Thrombosis; heart; antithrombin